The NGAL serum level in patient with contrast-induced nephropathy (CIN): a systematic review and meta-analysis - Amly, Harzalina Zilfi; Sitorus, Igna Laurensus; sitepu, Evi ananta ulisa (Publikasi Indonesia, 2024)
Contrast media are commonly injected into the bloodstream to increase image contrast and improve the diagnostic capabilities of radiological examinations. Contrast-induced nephropathy (CIN) is a severe complication of renal impairment after administration of contrast media. NGAL is a reliable early biomarker that has been studied in contrast to kidney damage and other conditions that affect the kidney. This study aimed to determine the mean difference in serum NGAL levels between patients with and non-CIN which will be used as the cutoff value for predicting CIN. The search was performed using three databases with the following eligibility criteria: (1) adult patients (> 18 years old), (2) patients who underwent the procedure with contrast medium injection, and (3) diagnosis of CIN based on the increase in serum creatinine level after contrast infusion. Meta-analysis was performed using a random-effect model. The mean difference (MD) and confidence interval of serum NGAL (ng/mL) between CIN and non-CIN after contrast media injection based on nine studies (1,293 subjects) was 84.14 (95% CI: 48.90, 119.38) ng/mL. Egger’s regression test showed significant asymmetry in the funnel plot (p < .0001). This study found a positive difference in serum NGAL levels between patients with and without CIN after contrast medium injection.